Encapsulation of Biologically Potent Neurotransmitters into HP-β-CD Probed by Physicochemical Approach simultaneously Optimized by Computational Studies (Journal of Scientific Research, 2024)
The inclusion complexes of the neurotransmitters, namely (±) epinephrine hydrochloride, dopamine hydrochloride, and tyramine hydrochloride in an aqueous medium, were studied physicochemically and spectroscopically. These rendered systems of drug delivery with the potential to ensure delivery to desired targets. The stoichiometry of the 1:1 ratio of host-guest binding was established using Job plots. Conductimetric studies gained an understanding of inclusion as a process. Furthermore, 1H NMR was used to characterize the inclusions, and the Benesi Hildebrand equation was applied to obtain the association constants. Thermodynamics, which are important in predicting the feasibility of any process, were in favor of inclusion as obtained by the evaluation of various thermodynamic parameters from Van᾿t Hoff's equation.